Autologous platelet‐rich plasma covering urethroplasty versus dartos flap in distal hypospadias repair: A prospective randomized study. (4th February 2019) - Mahmoud, Abdelaziz Yehya; Gouda, Samir; Gamaan, Ibrahim; Baky Fahmy, Mohamed A
Abstract : Objective: To compare the outcome and complication rate of the platelet‐rich plasma applied as a coverage layer and dartos flap layer during primary repair of distal hypospadias. Methods: A prospective randomized study was carried out comprising 180 boys (age range 12–65 months) from October 2011 to December 2016 at Al‐Azhar University Hospitals, Cairo, Egypt. A single surgeon carried out all urethroplasty. Patients were randomly divided into two groups: group A (tubularized incised plate urethroplasty with platelet‐rich plasma coverage layer) and group B (ventral dartos flap). Complication rates were compared between two groups. Results: There was a significant difference in the occurrence of complications between the two groups. A total of 36 (20%) complications were recorded in 26 patients, just 12 (13.3%) reported in group A, but 24 (26.7%) complications were reported in group B. Urethrocutaneous fistula was observed in nine patients (10%) in group A, and 12 (13.3%) in group B. Partial glans dehiscence occurred in one patient in group A, and four patients in group B. No patient in group A had a superficial wound infection, compared with six patients in group B. One case of meatal stenosis and urethral stricture was recorded in each group, all of which were managed conservatively. The resultant urinary stream was single and good in 154 patients of both groups. Conclusions: Platelet‐rich plasma sheet might be considered as an alternative coverage layer for distal hypospadias repair, especially in the absence of a healthy layer.